Oral Presentations Abstracts: CLINICAL ETHICS AND DISORDER OF CONSCIOUSNESS - DERCHI, Chiara-Camilla; CERUTI, Silvia; GIUBBILO, Ilaria (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Disorders of Consciousness (DOCs) identify a diverse group of dysfunctions affecting individuals who have survived severe brain damage. Although the clinical evaluation of patients with DOC normally depends on their residual ability to create a connection with the outside world through motor behavior, in the last ten years neuroscientists have made a great effort to better characterize the patient’s consciousness even in the case of reduced or no motor reactivity. Often, in fact, patients with DOCs are not able to perform any type of movement or adequately understand the command required but they might be still conscious or at least minimally conscious. The gap between patients’ motor capability and their residual brain complexity raises important moral issues, especially about appropriateness and proportionality of interventions and treatments. We argue that Clinical Ethics Consultation may be crucial in addressing these clinical scenarios, which assume aspects of further drama when the DOC derives from a sudden and unexpected acute event such as a trauma or a cerebrovascular accident in healthy patients. In these situations, given the particular vulnerability of the patients and the unpredictability of the diseases, Ethics Consultants should be involved in the therapeutic process in order to improve the standard of care, ensuring compliance with the inclinations and desires of the patients. Moreover, Ethics Consultants should monitor that the procedures are rigorously managed in the context of fully understood consent of those who are legally entitled to make decision.